2018
DOI: 10.1093/gerona/gly172
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Association Between Persistent Pathogens and Incident Depression Among Older U.S. Latinos

Abstract: Depression is estimated to affect over 6.5 million Americans 65 years of age and older and compared to Non-Latino Whites older US Latinos have a greater incidence and severity of depression, warranting further investigation of novel risk factors for depression onset among this population. We used data on 771/1789 individuals ≥ 60 years of age from the Sacramento Area Latino Study on Aging (1998-2008) who were tested for cytomegalovirus (CMV), herpes simplex virus, varicella zoster, Helicobacter pylori, Toxopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
0
19
1
Order By: Relevance
“…We have previously reported an association between T. gondii and depressive symptoms in this sample, even when adjusting for age, gender, region of residence, education, marital status, cat ownership, 12-month diagnoses, CRP, and antidepressant use [1]. Some previous studies have found CMV but not HSV-1 to be linked with depression [11,14,50], but the association between exposure to herpes infections and depressive symptoms has not been extensively studied.…”
Section: Discussionmentioning
confidence: 59%
“…We have previously reported an association between T. gondii and depressive symptoms in this sample, even when adjusting for age, gender, region of residence, education, marital status, cat ownership, 12-month diagnoses, CRP, and antidepressant use [1]. Some previous studies have found CMV but not HSV-1 to be linked with depression [11,14,50], but the association between exposure to herpes infections and depressive symptoms has not been extensively studied.…”
Section: Discussionmentioning
confidence: 59%
“…Considering the earlier cross-sectional associations of T. gondii with depressive symptoms, GAD and comorbid disorders in this study population (Suvisaari et al, 2017), and abundant literature documenting such associations in other populations (Pearce et al, 2012;Rector et al, 2014;Simanek et al, 2018b), the lack of association in this longitudinal setting was unexpected. However, our results are in line with a recent systematic review, which did not find an association between depressive disorders and T. gondii infection (Sutterland et al, 2015).…”
Section: Discussionmentioning
confidence: 68%
“…One of the few other longitudinal studies on the topic assessed infections and the risk of new-onset depressive symptoms, and found that CMV, but not HSV-1, varicella zoster, T. gondii or Helicobacter pylori predicted incident depression over a nine-year follow-up (OR 1.4), and the association was not mediated by CRP or IL-6 levels (Simanek et al, 2018b). In another population with a one-year follow-up, there was also an association between higher CMV, but not HSV-1, IgG antibody level and incident depressive symptoms (Simanek et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the well-established association between MDD, stress, and inflammation [1,2], it is conceivable that HCMV may be more prone to reactivation in MDD populations. Indeed, HCMV has been associated with depression in at least 13 studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53]. In our recent work, we found that HCMV infection was associated with reduced gray matter volume in participants with MDD but not healthy controls [54].…”
Section: Introductionmentioning
confidence: 67%